Influencia del sistema de información para comprensión lectora en el nivel de comprensión lectora de textos narrativos en los estudiantes del segundo grado de educación primaria de la institución educativa nº 00536 de rioja en el año 2012 - Meléndez Díaz, Jesús Edwar (2012)
The nowadays research was carried out whit second grade students of primary education in the E.I. 00536 belonging to the district and province of Rioja, San Martin Region. The problem, hypothesis and the general objective have been designed according to the variables: Independent, Information System for Reading Comprehension (ISRC); and dependent, levels of narrative texts of reading comprehension. The theoretical explanation about using of information and communication technology to improve the narrative texts of reading comprehension as well as the theoretical maintain of ISRC and its strategies to improve reading comprehension, it has been based in the language communicative approach, in the Rockart model, constructivist model of learning and cognitive approach of assessment of reading comprehension. It was formulated two hypotheses: The variable hypothesis whose presumption was a significant interaction, while the supposing null hypothesis was the lack of interaction. The sample was formed of forty students, it was used the Quasi-experimental design, the procedure consisted in the applying of a pre-test and a post-test such as for the control group as well as for the experimental. Carried out the contrasted hypothesis, the results showed a significant interaction using the ISRC. As a result of the conclusions shape their generality, specifying that experimental group improved their reading comprehension significantly, unlike control group that wasn’t significant.